2020
DOI: 10.3390/nu12103219
|View full text |Cite
|
Sign up to set email alerts
|

Ceruloplasmin and Coronary Heart Disease—A Systematic Review

Abstract: Several studies indicate that oxidative stress might play a central role in the initiation and maintenance of cardiovascular diseases. It remains unclear whether ceruloplasmin acts as a passive marker of inflammation or as a causal mediator. To better understand the impact of ceruloplasmin blood levels on the risk of cardiovascular disease, and paying special attention to coronary heart disease, we conducted a search on the two most commonly used electronic databases (Medline via PubMed and EMBASE) to analyze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…In addition to metabolism of copper and iron, Cp is involved in coagulation, angiogenesis, defense against oxidative stress, and iron homeostasis 15 . Recent studies reported that Cp is also associated with psoriasis, type 2 diabetes, coronary heart disease, and obesity 16 17 18 19 . Although the underlying mechanism has yet to be elucidated, hypothetically, it is likely that Cp mediates the pathogenic effects via apoptosis, cytotoxicity, cell replication, increased oxidative stress and pathogenic gene activation 20 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to metabolism of copper and iron, Cp is involved in coagulation, angiogenesis, defense against oxidative stress, and iron homeostasis 15 . Recent studies reported that Cp is also associated with psoriasis, type 2 diabetes, coronary heart disease, and obesity 16 17 18 19 . Although the underlying mechanism has yet to be elucidated, hypothetically, it is likely that Cp mediates the pathogenic effects via apoptosis, cytotoxicity, cell replication, increased oxidative stress and pathogenic gene activation 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an increase in serum copper and ceruloplasmin concentrations could also be the consequence of (sub‐)clinical inflammation and stress, but not necessarily the cause. However, the increase of serum copper, and secondarily of ceruloplasmin caused by myocardial infarction, seems not to be completely associated with an inflammatory response [163].…”
Section: Coppermentioning
confidence: 99%
“…Recently, it evidence has been provided that supports a direct relationship between elevated ceruloplasmin levels and CVD. Individuals with high ceruloplasmin serum concentrations are more likely to have CVD [ 64 ]. Most of the studies analyzed in a recent systemic review by Arenas de Larriva and collaborators [ 64 ] showed a direct relationship between serum ceruloplasmin levels and the incidence of CVD.…”
Section: Microrna and Cu Metabolism In Disease Statesmentioning
confidence: 99%
“…Individuals with high ceruloplasmin serum concentrations are more likely to have CVD [ 64 ]. Most of the studies analyzed in a recent systemic review by Arenas de Larriva and collaborators [ 64 ] showed a direct relationship between serum ceruloplasmin levels and the incidence of CVD. The higher the patient’s serum ceruloplasmin level, the more likely the patient is to experience CVD complications.…”
Section: Microrna and Cu Metabolism In Disease Statesmentioning
confidence: 99%
See 1 more Smart Citation